Collaborative Cross Mouse Population for Studying Alveolar Bone Changes and Impaired Glucose Tolerance Comorbidity After High‐Fat Diet Consumption. Issue 9 (1st September 2017) - Nashef, Aysar; Abu‐Toamih Atamni, Hanifa J.; Buchnik, Yuval; Hasturk, Hatice; Kantarci, Alpdogan; Stephens, Danielle; Wiess, Ervin I.; Houri‐Haddad, Yael; Iraqi, Fuad A.
Abstract : Background: High‐fat diet (HFD), body weight (BW) gain, and impaired glucose tolerance development are associated with alveolar bone loss (ABL) in susceptible individuals. This report explores the Collaborative Cross (CC) mouse population for studying the impact of genetic background on comorbidity of alveolar bone change and glucose tolerance after HFD consumption. Methods: Seventy‐eight mice from 19 different CC lines were maintained on rodent chow diet for 8 weeks and were subsequently transferred to an HFD (42% fat) for an additional 12 weeks. BW changes were assessed, and glucose tolerance was measured using an intraperitoneal glucose tolerance test (IPGTT). Six cytokines/chemokines were quantified by multiplex immunoassay, alveolar bone volume was quantified by microcomputed tomography, and the ABL phenotype was calculated relative to a control group (143 mice maintained on standard chow diet for 20 weeks). Results: The glucose tolerance response after HFD significantly varied among CC lines ( P <0.01), with a significant effect of sex ( P <0.01). Alveolar bone changes significantly varied among CC lines ( P <0.01). Overall, there was no significant correlation between alveolar bone volume changes and increased BW or glucose tolerance response. However, individual CC lines were identified that showed type 2 diabetes mellitus (t2DM) development and significant alveolar bone volume change ( P <0.05), whereas others showed t2DM development, regardless of periodontitis. Interleukin‐6 significantly correlated with alveolar bone changes ( P <0.05), whereas adipsin showed a negative correlation with IPGTT area under the curve values ( P <0.05). Conclusion: The present results demonstrate the power of CC mice for studying the genetic background impact between comorbidity of t2DM and bone loss.